Putative transformation of Neurospora os-1 protoplasts by a plasmid containing a G-481 phosphotransferase gene - C. P. Selitrennikoff; R. E. Nelson (Fungal Genetics Reports, 1984)
Putative transformation of Neurospora os-1 protoplasts by a plasmid containing a G-481 phosphotransferase gene